??STATISTICAL BOUNDEDNESS - Et, M.; Choudhury, C.; Debnath, S. (Isik University, 2025)
In this paper, we introduce and examine the concept of ??statistical boundedness and give some relations between statistical boundedness and ??statistical boundedness. We also introduce the notion of ??statistical upper bound, ??statistical lower bound, ??statistical supremum and ??statistical infimum and investigate their interrelationships. © Işık University, Department of Mathematics, 2025; all rights reserved.
Keywords: ??statistical boundedness; ??statistical convergence; ??statistical infimum; ??statistical supremum